Water pump optimization in an Internet of Things-based soil moisture monitoring system - Ode Putra, Aidil; Sukardi (Department of Electrical Engineering Universitas Negeri Padang, 2025)
Internet of Things (IoT) technology in agriculture is increasingly growing, especially in the automation of irrigation systems. This study aims to design and implement an IoT-based soil moisture monitoring system equipped with a water pump operation optimization algorithm to improve water use efficiency. This system is integrated with a NodeMCU ESP 8266 connected to the Blynk application and Google Spreadsheet to transmit data in real-time via smartphone devices. A combination of soil moisture sensors and water flow sensors is integrated to detect intelligent controls designed to automatically regulate the time and duration of watering based on the specified humidity threshold and predicted environmental conditions. Test results show that this system is able to maintain soil moisture levels within optimal limits while reducing water consumption significantly compared to conventional irrigation systems. Thus, this system not only supports more efficient and sustainable agricultural practices but also provides a technological solution that can be adapted to various scales of agricultural land